2015
DOI: 10.3892/or.2015.3820
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic effects of DNA vaccine encoding single-chain trimer composed of MHC I and vascular endothelial growth factor receptor 2 peptide

Abstract: Abstract. Vascular endothelial growth factor receptor 2 (VEGFR2)-mediated signaling is the key rate-limiting step in angiogenesis. VEGFR2 serves as the most important target of anti-angiogenic therapy for cancers. Single-chain trimer (SCT) comprising antigen peptide, β2-microglobulin (β2m), and major histocompatibility complex (MHC) class I heavy chain was a particularly powerful strategy involved in the increase of the potency of DNA vaccine against tumors and infections. In the present study, we constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Many recent preclinical studies have investigated the use of polyepitope DNA vaccines to reach a broad immune response. As a result, an increased IFNg production, a higher Th and CTL response [86, 87], and a general decrease in the tumor growth rate and metastasis formation were observed in different types of cancer models [88, 89]. Some preclinical studies focus on the HPV model, using DNA vaccines encoding E6 and E7 molecules [90], or E7 with a helper epitope [88].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent preclinical studies have investigated the use of polyepitope DNA vaccines to reach a broad immune response. As a result, an increased IFNg production, a higher Th and CTL response [86, 87], and a general decrease in the tumor growth rate and metastasis formation were observed in different types of cancer models [88, 89]. Some preclinical studies focus on the HPV model, using DNA vaccines encoding E6 and E7 molecules [90], or E7 with a helper epitope [88].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF and its receptor VEGFR2 have become popular subjects for study because of their role in angiogenesis. A number of studies on antitumor therapy with VEGFR2 as the target have demonstrated significant effects, including inhibition of tumor angiogenesis, tumor growth, and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Some anti-VEGF vaccines (CIGB-247: VEGF variant/bacterial adjuvant vaccine) showed reasonable tolerability in phase-I clinical trials with minimal hematopoietic or wound-healing impairments [151] . In addition, DNA and peptide based vaccines against VEGFR-2 showed potent humoral- and cellular-based anti-vascular immunity with subsequent anti-angiogenesis, anti-tumor and anti-metastatic responses [152] , [153] . These vaccines showed negligible adverse effects against wound healing and embryogenesis [153] .…”
Section: Anti-angiogenic Drug Families For Cancer Treatmentmentioning
confidence: 99%